2012
DOI: 10.1007/s11596-012-1058-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of nociceptive arcuate nucleus neurons in chloroquine-induced pruritic behaviors in mice

Abstract: Despite its clinical importance, the underlying central mechanisms of pruritic behaviors are poorly understood. To investigate the role of nociceptive arcuate nucleus neurons in chloroquine-induced pruritic behaviors in mice, we tested the effect of arcuate nucleus neurons and interscapular brown adipose tissue (IBAT) on itch produced by intradermal injection of chloroquine in the nape of the neck. Our results provide several lines of evidence for an important role of nociceptive arcuate nucleus neurons in chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Microinjections of intradermal CQ led to increased itch behavior and increased c‐fos expression, co‐localized with GRPR in arcuate nucleus neurons in mice . Further, CQ itch in mice is inhibited by NMDA receptor antagonists D‐AP5 IN Y142F Knock‐in mice, with associated increase in c‐fos colocalized with GRPR in same neurons …”
Section: Inferences and Potential Therapeutic Intervention Approachesmentioning
confidence: 94%
See 1 more Smart Citation
“…Microinjections of intradermal CQ led to increased itch behavior and increased c‐fos expression, co‐localized with GRPR in arcuate nucleus neurons in mice . Further, CQ itch in mice is inhibited by NMDA receptor antagonists D‐AP5 IN Y142F Knock‐in mice, with associated increase in c‐fos colocalized with GRPR in same neurons …”
Section: Inferences and Potential Therapeutic Intervention Approachesmentioning
confidence: 94%
“…Central itch mechanisms need to be probed further, as inhibition of itch at rostral brain levels may abolish itch regardless of the initiating cause. It appears that central NMDA mechanisms may be involved in CQ itch and act at a trigeminal region cephalic to spinal cord GRPR …”
Section: Inferences and Potential Therapeutic Intervention Approachesmentioning
confidence: 99%
“…They were briefly anesthetized with isoflurane (2% in 100% oxygen), and received an intradermal microinjection of 100 µl compound 48/80 (100 µg/100 µl) or saline in the nape of the neck (via a 0.3 ml insulin syringe with a 31 gauge needle). As previously described (12)(13)(14), immediately after the injection, the mouse was placed into the arena and videotaped from above for 30 minutes. Videotapes were reviewed by the observers of the pruritic behaviors.…”
Section: Behavioral Assaymentioning
confidence: 99%
“…Itch has been defined as an unpleasant skinspecific sensation with negative affective component, and produces a characteristic desire or reflex of scratching behavior [1][2][3]. The mechanisms that generate itch are poorly understood and effective treatment for chronic itch is lacking despite its clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral data suggest that scratching behavior may be used as an index for the study of itch in experimental rodents [2,14]. Several lines of evidence suggested that 5, 7-dihydroxytriptamine (5,7-DHT), a serotonergic neurotoxin, selectively diminished tissue 5-HT content [15][16][17].…”
Section: Introductionmentioning
confidence: 99%